CYBERSPACE AND ITS IMPACT ON THE GROWING GEOPOLITICAL POWER OF RUSSIA DURING THE ERA OF VLADIMIR PUTIN: A GEOPOLITICAL VISION - Dr. Ahmed Hassan Mejoul Al-Hasnawi (Scholar Express Journal, 2022)
Cyberspace is a new field of warfare in the modern era, as countries today urgently need to adapt to new technological threats, and they need to provide information to protect their sovereignty and develop their national strength, and policy makers need to understand the emerging climate of war and deal with it cautiously in light of the impact of the geographical field The political is how power and cyberspace interact. This relationship can be determined through the territories that they can control. Countries have access to new means of attack and espionage through the Internet, and these systems were not previously available in the context of achieving geopolitical sovereignty. Russian cyber-attacks on military and civilian infrastructure in the West, and the world as a whole, have become an ongoing challenge. This apparent shift in Russian foreign policy has re-emerged Russia as a great power and a powerful player on the international scene, with great capabilities to project geopolitical power that has been greatly amplified, which is a natural consequence. The behavior of the Kremlin developed during the era of President Vladimir Putin and its continuous demand for a distinct area around Russia’s immediate periphery, as well as its refusal to accept the security system after the Cold War in Europe, these developments showed Russia’s tendency to face risks above its weight along with its improved capabilities in various fields. This research is to shed light on the Russian cyber capabilities, and to answer the following questions: What is Russian cyberspace? What is its role in the growing geopolitical power of Russia? What is Putin's strategy in Russian cyberspace? What are the Russian cyber operations against the adversary countries, and what is Russia’s strategy in the cyber field in the future? These questions will be answered within the specified space for this research
Keywords: Cyberspace; Russia; Geopolitical Power; Vladimir Putin